Преобразовать выражение x^4+2*x^3+6*x^2+5*x=0,я выношу х ,и получается x(x^3+2x^2+6x+5)=0,а должно получится x(x+1)*(x^2+x+5)=0 -как это получить ?

medinehuseynzade medinehuseynzade    1   17.06.2019 03:50    1

Ответы
janamelnik10 janamelnik10  02.10.2020 03:10
x^4 + 2x³ + 6x² + 5x = 0

x^4 = x²x²
2x³ = x²x + xx²
6x² = 5x² + x²
5x = 5x

x²x² + x²x +  5x² + xx² + xx + 5x 
(xx² + xx+ 5x) = x(x² + x + 5)
x²x² +x²x + 5x² = x²(x² + x + 5)
(x² + x)(x²+x+5) = x(x+1)(x² + x + 5)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра